Postmodern Feminism in the Movie K-Pop Demon Hunters (2025) - Putu Marvitta Adira Prastiwi; Nissa Puspitaning Adni (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The South Korean entertainment industry, propelled by the global Hallyu wave, continues to thrive internationally. However, it remains influenced by deeply rooted patriarchal norms, especially in the portrayal of women in popular media. This study explores the representation of women in the film K-Pop Demon Hunters (2025) through the lens of Luce Irigaray’s postmodern feminist theory (1985). Using a qualitative content analysis approach, the research investigates the film’s visual, narrative, and symbolic dimensions to examine how female characters are depicted. Unlike the traditional portrayal of passive femininity prevalent in Korean popular culture, K-Pop Demon Hunters presents its female protagonists as active, autonomous, and empowered individuals. These characters express their identities through bodily performance, voice, dance, and emotion—an embodiment of écriture féminine, or feminine writing. The film introduces a symbolic language that allows women to speak from their own experiences, disrupting the male-dominated narrative structures often seen in mainstream media. Additionally, the film challenges patriarchal conventions by offering subversive and multifaceted representations of women’s bodies, relationships, and agency. Rather than reinforcing objectifying tropes, it constructs a space where feminine identity is fluid, expressive, and resistant to hegemonic definitions. This approach not only redefines the role of women within the cinematic narrative but also opens possibilities for alternative gender discourses in Korean media. In doing so, K-Pop Demon Hunters exemplifies how popular media can serve as both a mirror and a critique of societal gender norms.